RETURNABLE BAKING WASTE — A NEW TYPE OF RAW MATERIALS FOR DISTILLATES PRODUCTION (PART II. STAGE OF RAW MATERIALS PREPARATION FOR DISTILLATION) - L. N. Krikunova; E. V. Dubinina (Пищевые системы, 2020)
The processes that take place upon saccharified wort obtaining from the returnable baking waste and its fermentation was the research subject of this work. The development of operational parameters at the stage of returnable baking waste preparation for distillation, which provides a high-quality product is the purpose of the work. The samples of saccharified and fermented wort obtained from various bread and bakery products types produced by large enterprises in Moscow were the objects of the study. To characterize the composition of saccharified and fermented wort, the indicators to assess the quality of the wort from grain raw materials were used. The mass concentration of individual sugars in the wort was determined using high performance liquid chromatography on an Agilent Technologies 1200 Series device. The qualitative composition and volatile components concentration in the fermented wort was determined using gas chromatography on a Thermo Trace GC Ultra device. It was established that the percentage of solids transition to a soluble state does not depend on a returnable waste type and is in the range from 87.6% to 90.7%, and the starch transition to a soluble state, on the contrary, is determined by the processed raw materials type. It is shown that the use of rye-wheat bread after its preliminary enzymatic treatment with thinning and cytolytic drugs in a mixture with wheat bread in a ratio of 1÷1 to 1÷2 can improve the wort rheological characteristics and transfer from 98.1% to 99.3% starch of raw materials in a soluble state. It has been shown that for the efficient process of saccharified wort fermentation from returnable baking waste, the Fermiol and Turbo‑24 alcohol yeast races are most suitable, which ensure a high yield of ethanol and an optimal composition of volatile components in the fermented wort.